2012
DOI: 10.1128/jcm.00924-12
|View full text |Cite
|
Sign up to set email alerts
|

First Report of an Extensively Drug-Resistant VIM-2 Metallo-β-Lactamase-Producing Brevundimonas diminuta Clinical Isolate

Abstract: bIn the literature, only three Brevundimonas diminuta environmental isolates carrying metallo-␤-lactamase genes were recently published. However, so far, no B. diminuta clinical isolates carrying these carbapenem resistance genes have been described. Here we report the first VIM-2 metallo-␤-lactamase-producing B. diminuta clinical isolate obtained from an immunocompromised patient. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
(8 reference statements)
1
20
0
Order By: Relevance
“…[12][13][14] This case is the first reported peritonitis case in a peritoneal dialysis patient due to B. diminuta. Our patient has not any malignity and did not use any immunosupressed agent.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…[12][13][14] This case is the first reported peritonitis case in a peritoneal dialysis patient due to B. diminuta. Our patient has not any malignity and did not use any immunosupressed agent.…”
mentioning
confidence: 78%
“…This bacteria are usually susceptible to aminoglycoside, piperacillin-tazobactam and imipenem. [9][10][11][12][13][14] The true mechanisms of the resistance to various antibiotics are unclear. Carbapenem together with piperacillin/tazobactam may be the most reliable antibiotic for treating bacteriemia caused by Brevundimonas species.…”
mentioning
confidence: 99%
“…Some published studies have shown that; B. diminuta has variable resistance against some antimicrobial agents such as; azteronam, ciprofloxacin, ceftazidime (Gilad et al, 2000, Chi et al, 2004Han and Andrade, 2005;Choi et al, 2006;Almuzara et al, 2012). Susceptibility to the cefepime as 4 th generation of cephalosporins was reported in one case (Choi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In current study, azythromycin (exception one B. subvibrioides), gentamycin exhibited high affect in antibiogram process and could be considered as a treatment option. Detection of responsible genes or other mechanisms in our B. diminuta isolates need to more study (Almuzara et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation